Growing up a reader: Exploring children's and adolescents' perceptions of 'a reader'. Issue 2 (2nd April 2020) - McGeown, Sarah; Bonsall, Jane; Andries, Valentina; Howarth, Danielle; Wilkinson, Katherine; Sabeti, Shari
ABSTRACT: Background : Over the last two decades, the reading habits of children and adolescents have evolved. Research shows some similarities in the reading experiences of children and adolescents, but there are also differences. For example, adolescents are more likely to read digitally and generally report poorer attitudes towards reading. With this in mind, we asked: how do young people define a reader? Purpose : This small scale, in-depth study sought to understand how children and adolescents describe 'a reader' and examine similarities and differences in their responses. Methods : In total, 33 children aged 9–11 and 30 adolescents aged 15–16 from one primary school to one secondary school in the UK were individually interviewed, to explore their perceptions and descriptions of a reader. Using a participatory approach, adult researchers interviewed student researchers, who then in turn interviewed their peers. Transcribed data were analysed qualitatively, using a data-driven, inductive thematic analysis approach. Results : Our analysis revealed some common themes in terms of children and adolescents' perceptions of a reader. For example, readers were described as those who enjoy reading, read frequently, choose to read and, primarily, read print books. Readers were also described as those who are skilled at reading. However, subtle differences between children and adolescents were also found. For example, adolescents were more likely to say that readers choose a broader range of reading matter and did not need to read as frequently to be described a reader. Conclusions and implications : Our analysis offers insights into how children and adolescents defined a reader. Understanding more about how children and young people describe readers may help teachers who are working towards strengthening reading cultures in their primary or secondary school contexts. Broadening the conceptualisation of what it means to be a reader could arguably lead to a more inclusive use of the term and ultimately encourage more children and adolescents to self-identify as readers. Further, from a methodological point of view, we encourage researchers to consider a participatory research approach where appropriate, as this involvement in the research process can support primary and secondary school students in the development of their own research skills.